2020
DOI: 10.1007/s00296-020-04750-x
|View full text |Cite
|
Sign up to set email alerts
|

Performances of the “MS-score” And “HScore” in the diagnosis of macrophage activation syndrome in systemic juvenile idiopathic arthritis patients

Abstract: Macrophage activation syndrome (MAS) is a devastating complication of systemic JIA (sJIA), seen in approximately 10-25% of the sJIA patients. A number of criteria have been proposed to differentiate between activation of sJIA and MAS, including HScore and the recently proposed MS-score. This is the first study comparing the performances of MS-score and HScore for the diagnosis of MAS in sJIA patients. Systemic JIA patients followed at Hacettepe University Pediatric Rheumatology Unit were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…There was disagreement about one patient who had a MS score above the cut-off level of -2.1 but did not fulfil the 2016 MAS classification criteria and another patient who fulfilled these criteria but had a MS score below the threshold. Recently, Sag et al compared the MS-score and the HScore in seventy-one sJIA patients and found that the optimal cut-off for the MS-score in their cohort was ≥ -1.64 with a sensitivity of 91.3% and a specificity of 83.8% [ 26 ], being close to the optimal cut-off value at ≥ -1.5 (sensitivity = 71.4%, specificity = 91.7%) that was found in our cohort. The difference between the MS-score ≥ −2.1 presented by Minoia et al and the cut-off value in our study [ 16 ] may depend on selection bias and the small number of patients in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was disagreement about one patient who had a MS score above the cut-off level of -2.1 but did not fulfil the 2016 MAS classification criteria and another patient who fulfilled these criteria but had a MS score below the threshold. Recently, Sag et al compared the MS-score and the HScore in seventy-one sJIA patients and found that the optimal cut-off for the MS-score in their cohort was ≥ -1.64 with a sensitivity of 91.3% and a specificity of 83.8% [ 26 ], being close to the optimal cut-off value at ≥ -1.5 (sensitivity = 71.4%, specificity = 91.7%) that was found in our cohort. The difference between the MS-score ≥ −2.1 presented by Minoia et al and the cut-off value in our study [ 16 ] may depend on selection bias and the small number of patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…As the ferritin/ESR ratio only involves two tests, it is the easiest measure to identify MAS compared to the 2016 MAS classification criteria and MS score. However, a common disadvantage with all three sets of criteria is that they relate to a single time point and not changes in laboratory and clinical parameters over time [ 26 ]. Many have argued that relative changes in laboratory parameters are more useful for establishing an early MAS diagnosis than a certain threshold [ 5 , 8 , 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total score ranges between -8.4 to 41.8 with a value ≥-2.1 showing the best performance. Although the authors reported a good performance in a validation cohort, a separate study compared the MS score with the Hscore for identification of MAS in 71 patients with sJIA and found that the H-score performed slightly better [23].…”
Section: Classification Criteria and Diagnosismentioning
confidence: 96%